Molecular diagnostics of viruses in apple rootstocks using RT-qPCR - Askarova, M.A.; Yusupova, Z.Ya.; Madenova, A.K.; Abdikarimova, R.A.; Kabylbekova, B.Zh. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2026)
The development of intensive horticulture in Kazakhstan requires the use of virus-free planting material, particularly apple rootstocks (Malus domestica), free of viral and viroid infections. Latent forms of pathogens, which do not exhibit visible symptoms but are easily transmitted through vegetative propagation, are considered the most hazardous. The objective of this study was to evaluate the phytosanitary status of apple rootstocks used in nurseries in southern Kazakhstan by employing reverse transcription quantitative polymerase chain reaction (RT-qPCR). A total of 24 samples from field and laboratory collections were analyzed. RNA extraction was performed using the “PhytoSorb®” kit, and diagnostics were conducted on the Bio-Rad CFX96 platform using multiplex LETGEN test kits. Four pathogens were identified: Apple chlorotic leaf spot virus (ACLSV), Apple stem pitting virus (ASPV), Apple green crinkle associated virus (AGCaV), and Apple hammerhead viroid (AHVd). The viruses ASPV and AGCaV were found to be the most prevalent, occurring in both field and laboratory samples. These findings confirm the widespread circulation of these pathogens within the apple rootstock propagation system. The results emphasize the need for the implementation of regular molecular diagnostics, sanitation programs, and certification measures aimed at preventing the spread of latent infections and ensuring the sustainable development of horticulture in the region.
Алма телітушілеріндегі вирустық инфекцияларды RT-qPCR әдісімен анықтау
Молекулярная диагностика вирусов на подвоях яблони методом RT-qPCR
Keywords: Malus domestica; rootstock; viruses; viroids; RT-qPCR diagnostics